Identifying the Components of a Knowledge Management-Based Talent Management Model for Physical Education Teachers in Iraq - Al-Tamimi, Ahmed Abdulsalam Khalifa; Eghbali, Kebria; Ibrahim, Saif Harith; Nazari, Rasool (Digital Transformation and Administration Innovation, 2024)
This study aimed to identify the components of a knowledge management-based talent management model specifically tailored for physical education teachers in Iraq. A qualitative research design using grounded theory methodology was employed. Participants included 15 experts selected through purposive and snowball sampling, comprising experienced physical education teachers, sports management faculty, and administrative personnel from the Iraqi Ministry of Education. Data were collected through semi-structured face-to-face interviews and analyzed using Strauss and Corbin’s three-step coding approach: open coding, axial coding, and selective coding. The interview transcripts were systematically examined to extract codes, categories, and conceptual linkages that formed the basis of the emerging model. The analysis resulted in six core elements of the model. Causal conditions included meritocracy, cultural development, compensation systems, professional development, legal requirements, and transparency. Contextual conditions involved organizational support, technology infrastructure, strategic alignment, job-person fit, and managerial attitudes. Intervening conditions were identified as political barriers, financial constraints, legal rigidity, and organizational adaptability. Strategic responses comprised in-service training, external training, talent retention, talent development, recruitment and deployment, and structured identification systems. Core strategies centered on conceptualizing talent and establishing management structures. The outcomes included enhanced teacher motivation, extra-role behavior, knowledge creation, knowledge transfer, organizational commitment, succession planning, and the formation of knowledge-centered educational institutions. The findings underscore the critical role of knowledge management in modernizing talent management practices for physical education teachers in Iraq. The resulting model offers a comprehensive and context-sensitive framework that addresses institutional, procedural, and human factors in the teacher development process, with potential implications for broader educational reform efforts in similar socio-political contexts.